PERANCANGAN DESAIN KARAKTER DALAM PENDIDIKAN SEKSUAL MASA PUBERTAS UNTUK ANAK USIA 9-12 TAHUN - Dhicky Ramadhan (Universitas Negeri makassar, 2024)
This research aims to design characters for sexual education during puberty for children aged 9-12 years using qualitative research methods. In this study, we explore the opinions and preferences of the target audience through interviews and focus group discussions (FGDs) to understand their needs and preferences for character design. The results of interviews and FGDs are used as a basis for designing characters that are suitable for the understanding, interests, and visual styles desired by children in this age range. Through a qualitative approach, this research produces characters that are vibrant, striking, and easily remembered by children, as well as in line with the appropriate principles of sexual education for their developmental stage. These character designs are expected to be effective tools in conveying information about reproductive and sexual health to children, as well as helping them understand and cope with the changes that occur during puberty more effectively